Quantitative analysis of protein-RNA interactions by gel mobility shift - Ryder, Sean P. (2008)
The gel mobility shift assay is routinely used to visualize protein-RNA interactions. Its power resides in the ability to resolve free from bound RNA with high resolution in a gel matrix. In this chapter, we review the quantitative application of this approach to elucidate thermodynamic properties of protein-RNA complexes. Assay designs for titration, competition, and stoichiometry experiments are presented for two unrelated model complexes.